The Impact of Farm Animal Housing Restrictions on Egg Prices, Consumer Welfare, and Production in California. (13th September 2017) - Mullally, Conner; Lusk, Jayson. L.
Abstract: New animal welfare policies on the horizon in many U.S. states have prompted debates about the cost of achieving happier hens and hogs. A recent policy change in California offers a unique opportunity to measure the economic repercussions of minimum space requirements for egg‐laying hens. Using forecasting methods and structural break tests as applied to sixteen years of monthly data on egg production and input prices, we find that by July 2016, both egg production and the number of egg‐laying hens were about 35% lower than they would have been in the absence of the new regulations. Out‐of‐state eggs were able to compensate for falling California production until around the time the new rules were implemented, at which point imports of eggs into California fell. For consumers, we estimate price impacts using panel structural break tests and difference‐in‐differences models as applied to five years of scanner data from the retail market for shell eggs in three California markets and three control markets. We find that the average price paid per dozen eggs was about 22% higher from December 2014 through September 2016 than it would have been in the absence of the hen housing restrictions. The price impact fell over time, from an initial impact of about 33% per dozen to about 9% over the last six months of the observed time horizon. These price increases correspond to welfare losses of at least $117 million for the three California markets over the observed time horizon. Our results suggest that because of the policy change, California consumers can expect to experience annual welfare losses of at least $25 million in future years from higher retail egg prices alone.